Benign fibrous histiocytoma (cellular dermatofibroma) - Bonifazi, E.; Garofalo, L.; Mazzotta, F. (European Journal of Pediatric Dermatology, 2003)
Clinical features. Benign fibrous histiocitoma isthe cellular variant of dermatofibroma and is more frequent in childhood of the fibrous variant. The latter is the most frequent tumor in adults, especially inwomen (1). On light microscopy, benign fibrous histiocytoma is characterized by cells with round or oval nucleus and large, well demarcated cytoplasm, distributed according to a storiform pattern (3). In childhood the differential diagnosis should be made clinically with other more frequent proliferations, such as pilomatrixoma, which usually has a more irregular surface, and juvenile xanthogranuloma, usually arising more precociuously and rapidly undergoing xanthomization, and histologically with malignant fibrous histiocytoma, which presents greater cell polymorphism and atypical mitoses, and with dermatofibrosarcoma protuberans, which is barely demarcated and presents atypical mitoses.